Kompilasi Hukum Islam Ditinjau dari Perspektif Politik Hukum Indonesia - Muannif Ridwan; Saman Sulaiman; Abdul Bari Azed (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2021)
Research on the compilation of Islamic law (KHI) from the perspective of legislation has been carried out by many researchers and experts, therefore the author analyzes the compilation of Islamic law from the perspective of legal politic in Indonesia with reference to several legal political theories. The research method is qualitative (library research). Literature study is examining data by exploring, observing, examining, and identifying existing knowledge in the literature to get a conclusion of truth, both philosophical and empirical. This research concludes The compilation of Islamic law is a collection of various legal stances and opinions that have developed in the world of Islamic thought in Indonesia that have been well and wisely selected. KHI was formed because there is no agreed understanding regarding Islamic law in Indonesia. The position of KHI in Indonesia has been recognized by the State with the Presidential Instruction No. 1 of 1991 so that it has become a national law in Indonesia that applies to Muslims and becomes the main reference by religious judges in the Religious Courts to settle cases against people who are Muslim. Sociological analysis shows that the compilation of Islamic law is the government's responsiveness to the conditions of law enforcement, especially in the Religious Courts environment which at that time did not have a specific reference in carrying out its function as a technical judicial executor. Meanwhile, political analysis proves that the existence of the Compilation of Islamic Law is part of the legal political policy of the New Order government which seeks to reform in the field of law through codification and unification of law.